Moral and Physical Philosophy in Al-Ghazali's Islamic Thought: A Comparative Study through Western and Literary Perspectives - Refat Asaad Fathy Hodwa Eid; Zijian Zhao; Mahmudulhassan Mahmudulhassan; Sholihul Anwar; Sukisno Sukisno; Saidul Amin (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2026)
Al-Ghazali is one of the most influential philosophers in the history of Islamic thought. His thinking provides a profound synthesis between Physical Education and Moral Education, which is still relevant in contemporary intellectual discourse. This article discusses the complex relationship between moral education and physical education according to Al-Ghazali, using a critical comparative approach through the framework of Western philosophy and literature analysis. Through this study, it can be seen that the treasures of classical Islamic thought have provided an important foundation in answering various modern challenges, especially related to human development as a whole. The comparative approach used in this article confirms that Al-Ghazali's integrative vision remains of strong relevance in contemporary discussions of philosophy, ethics, and the role of physical education in moral formation.